The Formulation Of Community Policing Strategy To Settle Criminal Cases (Within community policing perspective) - Dody Eko Wijayanto; Koesno Adi; Masruchin Rubai (Universitas Islam Lamongan, 2013)
It is stipulated in the Criminal Law that only crime by accusation can be abrogated. On the other hand, common criminal cases must be processed within criminal justice system although it is only a minor legal offense. However, reality shows that minor legal offenses have often been put into a crime trial and community has often reacted against such a practice. This stimulates crime investigators to invent more peaceful ways to settle minor legal offenses although such ways are not acknowledged in criminal laws. Therefore, the Indonesian National Police have searched for a breakthrough to settle minor offenses by applying ADR in the form of penal mediation which puts the formulation of community policing strategy as the leading elementKeywords : Formulation, Community Policing, Settle Criminal